Análise da influência do ácido zoledrônico nos parâmetros fisico-químicos e morfoestruturais do tecido osseodentário de camundongos submetidos a modelo de osteonecrose dos maxilares - Lima Verde, Maria Elisa Quezado (2019)
Zoledronic acid (ZA) is incorporated into bone through its affinity for hydroxyapatite crystals, which can lead to structural and physico-chemical changes in mineralized tissues. The aim of this study was to analyze the physico-chemical and morphostructural properties of bone and dental tissue of mice submitted to a model of osteonecrosis of the jaws (OJ) related to chronic use of ZA. This is an experimental study, ex vivo, of a 2x2 factorial design, whose factors had two levels: male and female (sex) and ZA and Saline (treatment). The study had eight animals per group and was performed in duplicate. After three weekly administrations (days 0, 7, 14) of AZ 1.0 mg / kg or saline, the lower left 2nd molar (day 42) extraction was performed. Further administration was accomplished (day 49) and, subsequently, euthanasia (day 70). Samples were analyzed by Raman spectroscopy, conventional optical microscopy (histological and histomorphometric analysis), three-point bending test and computerized microtomography. Quantitative data (mean ± SEM) were compared using ANOVA 2-way / Bonferroni (sex and treatment), or one-way ANOVA and 2-way for repeated measures / Bonferroni, considering, for all analysis, p <0.05. The body mass of the animals, although increasing significantly with time, was not influenced by sex (p = 0.216) or treatment (p = 0.544). Treatment with ZA promoted histological alterations in femoral epiphyseal structure and increased the percentage of empty osteocytes and apoptotic osteoclasts, the number of total inflammatory cells and polymorphonuclear cells (p <0.05) at sites of exodontia. Additionally, animals treated with ZA had a significantly lower number and greater separation of bone trabeculae, as well as a smaller ratio between bone volume and tissue volume in alveolar trabecular bone. Females (ZA and saline) presented a significantly lower value of this parameter. Regarding the mechanical properties of femoral bone, sex and treatment factors exerted an independent influence, respectively, on the cross-sectional area (p <0.001 and p = 0.001), maximum load (p <0.001 and p <0.001) (p <0.001 and p <0.001) and work to fracture (p <0.001 and p = 0.030) parameters, being lower in females and increased in treated animals (ZA), which also presented higher flexural stiffness. Yield stress and flexural modulus, respectively, were higher in females (ZA and saline) (p = 0.004 and p = 0.001) and lower with ZA treatment (p = 0.038 and p = 0.007). Spectroscopic analysis showed an increase in crystallinity caused by ZA treatment in cortical and medullary regions of right and left hemimandibula, respectively, as well as femoral cortical, with statistical significance. There was a significant increase of crystallinity in dental enamel, coronary and radicular dentin with treatment (ZA). The factors interaction showed a decrease of hydroxyproline-to-proline ratio in coronary dentin and increased crystallinity in females radicular dentin. It is concluded that treatment with ZA, although associated with occurrence of OJ, modifies bone and dental mineral matrix, contributing to tissue biomechanics’ improvement. Females present differences in femoral biomechanical properties and have a lower density of trabecular bone in the post-dental extraction socket, when compared to males.